Continuous thermosalinograph oceanography along RV SONNE cruise track SO296/2 - Schlundt, Michael; Schulz-Vogt, Heide N (PANGAEA, 2024)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems, called self-cleaning monitoring boxes (SMBs). Usually, the SMBs are changed after ~24 hours. While temperature is taken at the water inlet in about 4 m depth, salinity is estimated within the SMB from conductivity and interior temperature. No temperature calibration was performed. Salinity was calibrated against discrete water samples from the inlet depth. For details to all processing steps see Data Processing Report.